Does non-linguistic segmentation still predict literacy in an L2 education? Statistical learning in Ivorian primary schools - Zinszer, Benjamin; Hannon, Joelle; Kouadio, Élise; AKPE, Yapo Hermann; Tanoh, Fabrice; Hu, Anqi; Qi, Zhenghan; Jasińska, Kaja (My University, 2023)
Statistical learning (SL) is a learning mechanism that does not directly depend on knowledge of a language, but predicts language and literacy outcomes for children and adults. Research linking SL and literacy has not addressed children who first learn to read in their second language (L2), common in primary schools worldwide. Several studies have linked SL with childhood literacy in Australia, China, Europe, and the U.S., and we pre-registered an adaptation for Côte d’Ivoire, where students are educated in French and speak a local language at home. Recruiting 117 sixth- graders from primary schools in several villages, we tested for correlations >0.3 between SL and literacy with 80-90% power. We found no evidence for these correlations, but visual SL was correlated with L2 phonological awareness. Although this finding may suggest a role of SL in emergent L2 skills, it underscores the need to include L2 acquisition contexts in literacy research.
Supplemental Materials: https://osf.io/6f8aw/
Keywords: Bilingualism; emergent literacy; literacy; phonological awareness; reading; second language acquisition; statistical learning